Comparative Analysis of the Efficacy of Dental Plaque Removal Between Manual and Powered Toothbrushes in Individuals With Syndactyly. Issue 6 (September 2018) - Kaizer, Rosane de Oliveira Fortes; Alves, Patrick Henry Machado; Tereza, Guida Paola Genovez; Dalben, Gisele da Silva; Neppelenbroek, Karin Hermana; Soares, Simone; Almeida, Ana Lúcia Pompéia Fraga de
Abstract : Objective: To compare the efficacy of dental plaque removal between manual and powered toothbrushes in individuals with syndactyly. Material and methods: Seventeen patients with Apert syndrome aged 11 to 30 years. The efficacy of toothbrushing was evaluated by the O'Leary plaque index at 2 periods: initial (before toothbrushing) and final (immediately after toothbrushing), using manual toothbrush (Colgate Twister) and powered toothbrush (Colgate Actibrush). Means were compared by the ANOVA test at a significance level of 5%. Results: The reduction in the plaque index was different for each type of toothbrush (interaction factor between manual and powered toothbrushes and initial and final periods, P  = 0.026). The powered toothbrush provided greater reduction of dental plaque than the manual toothbrush. Conclusion: In individuals with syndactyly, both manual and powered toothbrushes allowed significant plaque reduction on tooth surfaces; however, the powered toothbrush exhibited greater efficacy of plaque removal compared with the manual toothbrush.